PENGARUH LATIHAN SCISSOR JUMP TERHADAP POWER OTOT TUNGKAI TIM SEPAK TAKRAW PUTRA PPLP KABUPATEN SIAK - Raudatul Hadlen; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this study is that there are still many shortcomings in the PPLP men's takraw soccer team in Siak Regency, namely the lack of leg muscle power. The purpose of this study was to provide the Effect of Scissor Jump Exercise on Leg Muscle Power of the PPLP Sepak Takraw Putra team in Siak Regency. The study was conducted at the Siak Sport hall in Kualian street, Siak Sri Indrapura. This research was conducted from December 2018 to June 2019 with a frequency of exercise three days in one week. The population in the study was also a sample of the PPLP Sepak Takraw Putra Team in Siak Regency. The data obtained were analyzed descriptively, then the next research hypothesis was tested which had been submitted according to the problem, namely: "there is the effect of the Scissor Jump (X) exercise on increasing Power (Y). Based on the analysis carried out, the value of t counts between the initial test and the final test of Scissor Jump training on leg muscle power with t table at a significant level of 0.05 with degrees of freedom N - 1 (10-1 = 9). This shows that the value of t count (9.69)> t table (1,812) thus it can be concluded that the hypothesis states that there is the effect of Scissor Jump (X) training on the Power (Y) of the PPLP men's takraw soccer team in Siak Regency.Key Words: Scissor Jump Exercise, Power of Leg Muscle Power